Assessment of the influence of ICT facilities for sustainability of modern teaching excellence in education - Idriss, Ibrahim Dahiru; Maitma, Jaafar Zubairu; Haruna, Usman; Adamu, Adamu Mamman; Barde, Abubakar Idriss; Abubakar, Adamu (2020)
The advents of information and communication technology (ICT) have induced tremendous changes in the present education system. These interactive technological gadgets have affected the very nature of teaching and learning. Most teachers as well as studentsare not aware of the influence of ICT in the developing nations. Therefore the aim of this study is to determines the types of ICT facilities that could be affordable for the students and teachers, the extent of use of the ICT facilities among teachers ofSecondary Schools (senior) in Potiskum Local Government, the influence of ICT facilities among students in secondary schools in Potiskum, the influence of ICT facilities among teachers in secondary school in Potiskum, as well as the problems affecting theuse of ICT in teaching, learning and research in Potiskum. Findings of this study reveals that ICT gadgets are considered to be used in teaching and learning primary education but not affordable to teachers and students, students and teachers also do stayon computers but not for so long. ICT is also considered to have influenced teaching and learning in secondary schools. Therefore it is concluded that, students and teachers in secondary schools use ICT instruments in the process of teaching and learning,although the tools are not very much affordable to them. The study has also revealed that students and teachers do stay on computers a little period of time due to lack of ICT facilities in their schools. We therefore concluded that ICT gadgets should be considered of paramount priorities in schools as it influence teaching and learning and school authorities should find ways to make ICT gadgets available for use to both students and teachers to facilitate academic activities and to influence learning at large